2018
DOI: 10.1124/mol.117.111047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Farnesoid X Receptor Activation on Arachidonic Acid Metabolism, NF-kB Signaling, and Hepatic Inflammation

Abstract: Inflammation has a recognized role in nonalcoholic fatty liver disease (NAFLD) progression. In the present work, we studied the effect of high-fat diet (HFD) on arachidonic acid metabolism in the liver and investigated the role of the farnesoid X receptor (FXR, NR1H4) in eicosanoid biosynthetic pathways and nuclear factor light-chain enhancer of activated B cells (NF-kB) signaling, major modulators of the inflammatory cascade. Mice were fed an HFD to induce NAFLD and then treated with the FXR ligand obeticholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 38 publications
2
63
0
Order By: Relevance
“…A similar pattern was observed in our mouse model of NAFLD. Mice fed a HFD over 16 weeks gained up to 50% more weight than the mice on chow diet (Figure ), and showed signs of steatohepatitis, as previously described . A time‐dependent increase in the circulating levels of 1‐deoxysphingolipids, especially 1‐deoxySO, in mice fed the HFD compared with the normal chow group was observed (Figure D‐G), suggesting that 1‐deoxysphingolipids may be involved in the chronic, progressive hepatic damage that occurs in NAFLD.…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…A similar pattern was observed in our mouse model of NAFLD. Mice fed a HFD over 16 weeks gained up to 50% more weight than the mice on chow diet (Figure ), and showed signs of steatohepatitis, as previously described . A time‐dependent increase in the circulating levels of 1‐deoxysphingolipids, especially 1‐deoxySO, in mice fed the HFD compared with the normal chow group was observed (Figure D‐G), suggesting that 1‐deoxysphingolipids may be involved in the chronic, progressive hepatic damage that occurs in NAFLD.…”
Section: Resultssupporting
confidence: 70%
“…FXR has been associated with various effects on energy homoeostasis, including regulation of lipid metabolism and insulin sensitivity, which in turn can contribute to liver protection. 14,22,23 In the present study, we showed that mice fed a HFD exhibited characteristics of NAFLD and had increased levels of 1-deoxysphingolipids, both in the blood and in the liver. Accumulation of 1-deoxysphingolipids has been shown to promote hepatocyte apoptosis and mitochondrial damage both in vivo and in vitro.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations